Citrus tristeza virus - Yokomi R.K. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
This article describes various aspects of the citrus tristeza virus : identity, hosts, identification, geographic distribution, biology and ecology, pest significance and control.